2022
DOI: 10.3390/ph15060724
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization and Evaluation of the Antitumoral Activity of a Phospholipase A2 from the Snake Bothrops moojeni

Abstract: Nature presents a wide range of biomolecules with pharmacological potential, including venomous animal proteins. Among the protein components from snake venoms, phospholipases (PLA2) are of great importance for the development of new anticancer compounds. Thus, we aimed to evaluate the PLA2 anticancer properties from Bothrops moojeni venom. The crude venom was purified through three chromatographic steps, monitored by enzymatic activity and SDS-PAGE (12%). The purified PLA2 denominated BmPLA2 had its molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Another example is aurein peptides 1.2 and 3.1 from Litoria sp., which showed activity against the NCI cancer cell line, with LC 50 values of 4 and 10 μM, respectively [ 67 ]. Furthermore, data on RD cells and peptides are scarce in the literature nonetheless, recent studies have shown that phospholipase (BmPLA2) from Bothrops moojeni demonstrated an IC 50 of ~0.14 μM [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another example is aurein peptides 1.2 and 3.1 from Litoria sp., which showed activity against the NCI cancer cell line, with LC 50 values of 4 and 10 μM, respectively [ 67 ]. Furthermore, data on RD cells and peptides are scarce in the literature nonetheless, recent studies have shown that phospholipase (BmPLA2) from Bothrops moojeni demonstrated an IC 50 of ~0.14 μM [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the conformational changes in hydrophobic or hydrophilic environments for antimicrobial peptides through circular dichroism [ 64 , 65 , 66 ]. The CD analyses show that, in a hydrophobic environment, the conformational preference for Ca-MAP1 was α-helix, indicating that its structure favors the mechanism of action of the membrane permeabilization, as demonstrated in the Sytox Green assay.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds from animal venom have equal biotechnological importance; the Brazilian snake Bothrops moojeni produces an important phospholipase, A2, which can be collected due to its anticancer effects, at a concentration of 9.2 µM, in many cancers cell lines, including lung mucoepidermoid carcinoma NCI-H292 [ 65 ]. Another example is the wasp and bee venom of the species Vespa velutina , which possess antibacterial activity in Gram-negative and -positive bacteria, and anti-inflammatory activity in LPS-induced BV-2 inflammation at concentrations of 0.5 to 20 µg.mL −1 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…BmPLA 2 isolated from Bothrops moojeni venom showed anticancer activity against human epithelial colorectal adenocarcinoma (Caco‐2) and human rhabdomyosarcoma (RD) cell lines compared to controls (human fibroblast MRC‐5 and microglia BV‐2 cells) (Frihling et al, 2022). Using the IC 50 of BmPLA 2 against Caco‐2 and the controls, the selectivity index of 1.85 (when compared to MRC‐5) and 6.33 (when compared to BV2) was calculated, suggesting its promise as a potential anti‐tumour agent.…”
Section: Anticancer Effects Of Individual Snake Venom Toxinsmentioning
confidence: 99%